Preservation of Traditional Arts in Growing Love of Local Culture - Nendi, Ikhsan (Devotion : Journal of Research and Community Service, 2020)
This study aims to describe various problems related to the preservation of traditional arts at the Klapa Jajar Art Studio, Pekalipan Village, Cirebon City. In this study the authors used a qualitative descriptive research method. The author saw firsthand the problems that existed in the Klapa Jajar art studio, Pekalipan Village, Cirebon City. Then the author developed specifically the problems that were in place and made an Innovation Design in the form of implementation. Data collection techniques were carried out by direct interviews and documentation and direct observation. Based on the results of the above research, it can be concluded that in an effort to preserve traditional arts there are problems related to art marketing, promotion and a lack of interest in preserving arts from cultural elements. The preservation of traditional arts as an effort to foster the love of local culture in the Klapa Jajar art studio has an effect on the progress and preservation of art that has been dim for the last few years and supports people's interest in advancing their own local arts. The form of preservation of traditional arts as an effort to foster the love of Cirebon local culture in the Klapa Jajar art studio can be started from various elements in society to be invited to be pro-active in supporting conservation efforts by optimizing the media for art documentation